Computer modeling of exhaust jet flux interaction with deflecting shield - O. A. Kartishev (Научный вестник МГТУ ГА)
Method of exhaust jet flux interaction with deflecting shield computer modeling is proposed in this article. The article is devoted to concrete ecological task - to decrease the noise influence on ground maintenance stuff and passengers in the airports. The method is based on the Reynolds equation system solution obtained with the help of control volume method. Calculation results give an opportunity to choose main deflecting shield parameters according to concrete airport conditions.